Encapsulation of protein-based bioactive from black soldier fly for ruminant feeding - Uswatun Muslykhah; Srisan Phupaboon; Chaichana Suriyapha; Maharach Matra; Metha Wanapat (Journal of Agriculture and Food Research)
The increasing global population and subsequent animal protein source demand necessitate the exploration of alternative feed sources for animal. Insects have emerged as a viable option due to their potential to provide high-quality proteins with minimal environmental impact. Black soldier fly (BSF), containing high nutrients such as protein and bioactive compound, influenced by growth stage and dietary factors, thus providing a substantial reservoir of essential amino acids and other bioactive compounds crucial for ruminant. However, these components are sensitive and require protection from the degradation in the rumen. Under the processing and delivery of those compounds, in addition to keeping and enhancing the functionality of the bioactive compounds, coating or protection should be implemented. Encapsulation, which has recently garnered attention for its potential technology in animal feed nutrition, offers promise in protecting sensitive components through their stability, protection, and controlled release within specific organs. This review article aims to investigate the application of encapsulation techniques for protein extracts derived from black soldier fly larvae to enhance their effectiveness and utilization in ruminant feeding. Additionally, the review consolidates studies on the transformation processes of the nutrition values of various edible insects, the method of processing black soldier fly, BSF protein extraction process, and the encapsulation technique. In conclusion, the encapsulation of protein extracts from black soldier fly larvae represents a promising BSF-derived protein to provide sustainable and effective alternatives for improving ruminant nutrition in the future.